การพัฒนาสื่อเพื่อส่งเสริมภาพลักษณ์และบทบาทของศูนย์การเรียนรู้ชุมชน วัดอรุณราชวราราม กรุงเทพมหานคร Media Development For Image And Role Promotion Of The Community Learning Center, Wat Arunrachawararam (The Dawn Temple), Bangkok - ภูงามดี, สกนธ์ (Journal of Fine and Applied Arts Khon Kaen University, 2015)
การวิจัยเรื่อง การพัฒนาสื่อเพื่อส่งเสริมภาพลักษณ์และบทบาทของศูนย์การเรียนรู้ชุมชน วัดอรุณราชวราราม กรุงเทพมหานคร มีวัตถุประสงค์ 4 ประการ คือ 1) เพื่อศึกษาความเป็นมาและผลสำเร็จของของศูนย์การเรียนรู้ชุมชน วัดอรุณราชวราราม กรุงเทพมหานครโดยละเอียด 2) เพื่อศึกษาความต้องการในการใช้สื่อประชาสัมพันธ์เพื่อประโยชน์สูงสุดของศูนย์ฯ 3) เพื่อออกแบบสื่อเพื่อส่งเสริมภาพลักษณ์และบทบาทของศูนย์ฯ และ 4) เพื่อเสนอแนวทางการใช้สื่อส่งเสริมภาพลักษณ์และบทบาทของศูนย์ฯ ให้มีประสิทธิภาพและประสิทธิผลมากขึ้น ประเภทสื่อที่เป็นเป้าหมายด้านผลผลิตของโครงการวิจัย ได้แก่ ผลงานต้นแบบสื่อที่ออกแบบโดยผู้วิจัย ประกอบด้วย 1) โบรชัวร์ 2) ใบปิดโฆษณา 3) ป้ายโฆษณา และ 4) ภาพและข้อมูลโฆษณาทางเว็บไซต์ วิธีการวิจัย ประกอบด้วย การสัมภาษณ์แบบเจาะลึก จำนวน 2 ครั้ง และการประชุมกลุ่มย่อยเพื่อระดมความคิดเห็นแบบการสนทนากลุ่ม จำนวน 2 ครั้ง จากนั้นนำผลที่ได้ไปเป็นข้อมูลสำคัญในการออกแบบผลงานต้นแบบสื่อตามวัตถุประสงค์ของการวิจัย ผลการวิจัยสรุปได้ 5 ประการ คือ ประการที่ 1 ภารกิจหลักของศูนย์การเรียนรู้ชุมชน วัดอรุณราชวราราม กรุงเทพมหานคร คือ ให้การศึกษาแบบอาชีวศึกษาแก่เยาวชนยากจนและด้อยโอกาส ที่จบการศึกษาระดับมัธยมศึกษาตอนปลายจากโรงเรียนศึกษาสงเคราะห์ในจังหวัดต่างๆ ที่สังกัดกระทรวงศึกษาธิการ โดยสื่อเดิมของศูนย์ฯ มีเพียง 3 ประเภท คือ 1) โบรชัวร์หรือแผ่นพับซึ่งจัดทำเองโดยการถ่ายสำเนาหมึกขาว-ดำ 2) ป้ายไวนิลที่ติดตั้งบริเวณด้านหน้าของศูนย์ฯ และ 3) ข้อความบน Facebook หรือ Blog สนทนาต่างๆ ทางอินเตอร์เน็ต โดยศูนย์ฯ ยังไม่ได้จัดทำเว็บไซต์ของศูนย์ฯ อย่างเป็นเอกเทศ ส่วนความต้องการด้านสื่อของศูนย์ คือ ต้องการให้พัฒนาสื่อ 4 ประเภท คือ โบรชัวร์ ใบปิดโฆษณา ป้ายโฆษณา รวมทั้งสื่อบนเว็บไซต์ ประการที่ 2 ผลการทดสอบคุณภาพของผลงานต้นฉบับสื่อฉบับแรก ที่ออกแบบโดยผู้วิจัย ภายใต้เกณฑ์การทดสอบสื่อ 5 ด้าน สรุปได้ว่า สื่อทุกประเภท 1) มีความสวยงาม 2) กลุ่มเป้าหมายมีความสะดวกในการได้รับข้อมูลจากสื่อ 3) มีปริมาณข้อมูลที่เหมาะสมกับการรับรู้ของกลุ่มเป้าหมาย 4) “สาร” (Message) ที่ปรากฏในสื่อมีประโยชน์ต่อการสื่อสารบทบาทและภาพลักษณ์ของศูนย์ ฯ และ 5) สามารถโน้มน้าวกลุ่มเป้าหมายให้สนใจรับคำแนะนำและสอบถามข้อมูลเพิ่มเติม ประการที่ 3 ข้อควรปรับปรุงเพิ่มเติมในผลงานต้นฉบับสื่อฉบับแรก โดยสรุป คือ 1) ในสื่อทุกประเภท ควรเพิ่มข้อความที่เป็นตัวอักษรในลักษณะสโลแกน ของศูนย์การเรียนรู้ชุมชน วัดอรุณราช วราราม เพื่อสร้างการจดจำในด้านบทบาทและภาพลักษณ์ของศูนย์ฯ ควรเปลี่ยนภาพเป็นภาพของนักเรียนที่เรียนในศูนย์ฯ เพื่อสื่อสารข้อมูลที่เป็นสภาพจริงมากขึ้น ควรเพิ่มตราสัญลักษณ์ (โลโก้) ของศูนย์ฯ และของวัดอรุณราชวราราม ไว้คู่กัน และควรแก้ไขชื่อเว็บไซต์และที่อยู่ทางอีเมล์ของศูนย์ฯ ให้ถูกต้อง และ 2) เฉพาะสื่อที่เป็น โบรชัวร์ ให้เพิ่มข้อความ 2 ข้อความที่ระบุถึงการได้รับเกียรติบัตรเมื่อจบการศึกษา ประการที่ 4 การปรับปรุงสู่ผลงานต้นแบบสื่อ ฉบับสมบูรณ์ ผู้วิจัยได้ปรับปรุงผลงานต้นแบบสื่อ ฉบับสมบูรณ์ที่พัฒนาขั้นสุดท้าย โดยประกอบด้วยสื่อตามความต้องการของศูนย์ฯ 4 ประเภท และผู้วิจัยออกแบบเพิ่มเติมอีก 1 ประเภท รวมเป็นสื่อ 5 ประเภท ดังนี้ 1) โบรชัวร์ 2) ใบปิดโฆษณา 3) ป้ายโฆษณาขนาดใหญ่ 4) โฆษณาบนเว็บไซต์ และ 5) ป้ายแบนเนอร์ ประการที่ 5 แนวทางการใช้สื่อส่งเสริมภาพลักษณ์และบทบาทของศูนย์การเรียนรู้ชุมชน วัดอรุณราชวราราม กรุงเทพมหานคร ประกอบด้วย (1) สถานที่นำเสนอสื่อ ซึ่งได้แก่ ภายในวัดอรุณราชวราราม บริเวณหน้าศูนย์ฯ หน่วยงานใกล้เคียงเช่นสำนักงานเขตบางกอกใหญ่ รวมทั้งหน่วยงานที่เกี่ยวข้องคือ โรงเรียนการศึกษาสงเคราะห์ทั่วประเทศ และ (2) ระยะเวลาในการนำเสนอสื่อ โดยเน้นการนำเสนอสื่อทุกประเภทอย่างต่อเนื่องตลอดทั้งปี ทั้งนี้ ผู้วิจัยได้มอบเอกสารแนวทางการใช้สื่อส่งเสริมภาพลักษณ์และบทบาทของศูนย์การเรียนรู้ชุมชน วัดอรุณราชวราราม พร้อมแผ่นบันทึกข้อมูล (DVD) ผลงานต้นแบบสื่อ ฉบับสมบูรณ์ ให้แก่ผู้แทนศูนย์ดังกล่าวเป็นที่เรียบร้อยแล้ว This research entitled “Media Development for Image and Role Promotion of the Community Learning Center, Wat Arunrachawararam (The Dawn Temple), Bangkok” was officially funded, within 2012 budget plan, by Strategic Wisdom and Research Institute (Srinakharinwirot University) and National Research Council of Thailand. The objectives of the research were 1) to study background and achievement of the Community Learning Center, Wat Arunrachawararam (The Dawn Temple), Bangkok 2) to examine the Center’s needs for media improvement 3) to develop the media for better image and role promotion of the Center and 4) to recommend the media application guideline for better image and role promotion of the Center. The main outputs of the research were the manuscripts of four media types which were; 1) brochure 2) poster 3) billboard) and 4) website advertisement. Main research methods included; 1) in-depth interview and focus group discussion and 2) media development in form of media manuscripts. The results were as the followings; 1. Core missions of the Community Learning Center, Wat Arunrachawararam (The Dawn Temple), Bangkok have been 1) vocational education support provided for needy youths in Thailand with vocational programs and 2) social responsibilities provided for people (both Thai and foreigners) with short term of meditation practice and job trainings. At present, the Center has applied only three types of media which were; black-and-white copy of brochure, simple vinyl signs and temporary message blog in facebook, without the Center’s own website. The Center needed more types of media to help promote its image and role, namely; 1) brochure 2) poster 3) billboard) and website advertisement. 2. Results of media testing towards the first draft of media manuscript, designed by the researcher, were reflected by these following characteristics; 1) beautiful colors for target group attraction 2) easy accessibility for message receiving via the media 3) sufficient volume of the right information for target group perception 4) useful message for enhancing the Center’s image and role promotion and 5) persuasive looks for generating future contacts for additional information. 3. The Center’s suggestions for first-draft-media-manuscript improvement were; 1) all types of media should be added with the Center’s slogan, logos (of the Center and the temple), correct spelling of the Center’s website and e-mail address and 2) only in “brochure” should be added with two sentences, one was “Graduates of Assistant Nurse Program will confer a certificate from Siam University” and the other was “Graduates of Electronic Program will confer a certificate from Thonburi Vocational College” 4. The improvement for launching final media manuscript was made and finished upon the Center’s needs and suggestions. The finished outputs following the research’s objectives were five types of media; four types was requested by the Center’s needs and the other one was favorably added by the researcher, which were 1) Brochure (three fold); 210 x 297 millimeter. or A4 paper sized 2) Poster, 65 x 50 centimeter. 3) Billboard; 1.5 x 2.0 meter 4) Website; with suitable size following the Internet System Provider’s arrangement and 5) Banner; 1.5 x 3.0 meter. 5. Media application guideline for better image and role promotion of the Center was recommended by the researcher; 1) places for media presentation were inside Wat Arunrachawararam, in front of the Center, on notable boards of related organizations such as Bangkok Yai District Office or networking schools and 2) Time for media presentation was continuous period of time through the year. In final stage of research procedure, the document of media application guideline and DVD of final media manuscript were given to the Center’s Director.